Current challenges and the diagnostic pitfalls in the grading of epithelial dysplasia in oral potentially malignant disorders: A review - Sonia Gupta; Manveen Kaur Jawanda; GS Madhushankari (Elsevier, 2020)
Oral cancer is one of the common cancers in the world causing high morbidity. Development of cancer is preceded by certain asymptomatic clinical lesions and conditions all together known as 'oral potentially malignant disorders'. Histologically they are represented by the term 'oral epithelial dysplasia'. The degree of severity of dysplasia is determined in the form of 'grade'. Despite the existence of several grading systems proposed by various scholars, it is still a challenging task for the Pathologists to grade dysplasia accurately for the proper diagnosis of the disease and to follow preferable treatment plans. This review aims to focus on the current challenges and the diagnostic pitfalls in the grading of oral epithelial dysplasia in various oral potentially malignant disorders.